Autosomal dominant lamellar ichthyosis due to a missense variant in the gene NKPD1 - Komlosi, Katalin; Glocker, Cristina; Hsu-Rehder, Hao-Hsiang; Alter, Svenja; Kopp, Julia; Hotz, Alrun; Zimmer, Andreas David; Haußer-Siller, Ingrid; Sandhoff, Roger; Oji, Vinzenz; Fischer, Judith (The journal of investigative dermatology, 2024)
The identification of monogenic causes for cornification disorders has enhanced our understanding of epidermal differentiation and skin barrier function. Autosomal dominant lamellar ichthyosis is a rare condition, and ASPRV1 was the only gene linked to autosomal dominant lamellar ichthyosis to date. We identified a heterozygous variant (ENST00000686631.1:c.1372G>T, p.[Val458Phe]) in the NKPD1 gene in 7 individuals from a 4-generation German pedigree with generalized lamellar ichthyosis by whole-exome sequencing. Segregation analysis confirmed its presence in affected individuals, resulting in a logarithm of the odds score of 3.31. NKPD1 encodes the NKPD1 protein, implicated in the plasma membrane; its role in human disease is as yet unknown. Skin histology showed moderate acanthosis and compact orthohyperkeratosis, and the ultrastructure differed clearly from that in ASPRV1-autosomal dominant lamellar ichthyosis. Although NKPD1 mRNA expression increased during keratinocyte differentiation, stratum corneum ceramides exhibited no significant changes. However, affected individuals showed an elevated ratio of protein-bound ceramides to omega-esterified ceramides. This highlights NKPD1's role in autosomal dominant lamellar ichthyosis, impacting ceramide metabolism and skin lipid barrier formation, as demonstrated through functional characterization.